Re-imagining contested communities : connecting Rotherham through research - Campbell, Elizabeth, 1962-; Pahl, Kate; Pente, Elizabeth; Rasool, Zanib (Connected communities (Bristol, England), 2018)
"This is a book that challenges contemporary images of 'place'. Too often we are told about 'deprived neighbourhoods' but rarely do the people who live in those communities get to shape the agenda and describe, from their perspective, what is important to them. In this unique book the process of re-imagining comes to the fore in a fresh and contemporary look at one UK town, Rotherham. Using history, artistic practice, writing, poetry, autobiography and collaborative ethnography, this book literally and figuratively re-imagines a place. It is a manifesto for alternative visions of community, located in histories and cultural reference points that often remain unheard within the mainstream media. As such, the book presents a 'how to' for researchers interested in community collaborative research and accessing alternative ways of knowing and voices in marginalised communities."--